A novel cell-permeable RDP-p53 fusion protein for specific inhibition on the growth of cancerous neural cells. (1st September 2016) - Wu, Jing; Zhang, Enqi; Fu, Ailing
Abstract: Objective : There is 25–35% mutation rate of p53 in cancerous neural cells and this rate reaches 70–76% in glioma cell line. Complement of wild-type p53 has become a potential strategy for protein therapy of cancerous neural cells. Here we investigated the feasibility of a novel RDP-p53 fusion protein for anti-proliferation of cancerous neural cell and the possible mechanism, which would provide an effective approach for targeted delivery of p53 protein to treat cancerous neural cells. Methods : The RDP-p53 fusion proteins are expressed in Escherichia coli, and they are labeled with FITC and rhodamine B by chemical modification. The fluorescence-labeled proteins are added to human hepatocellular carcinoma cells (HepG-2) and human neuroblastoma cells (SH-SY5Y) in order to investigate the possibility of RDP enhancing the cell uptake efficiency into neural cells as a cell-permeable carrier. The inhibitory effect of RDP-p53 on SH-SY5Y and human glioma cells (U251) was evaluated by MTT assay. Moreover, the anti-proliferation mechanism of RDP-p53 was determined by Apoptosis and Necrosis Assay Kit and flow cytometric analysis. Results : The results showed that RDP-p53 could enter SH-SY5Y cells with high efficiency and selectively inhibit the growth of cancerous neural cells, including SH-SY5Y and U251. Also, cell apoptosis pathway and cell-cycle arrest at the G2/M phase were associated with the inhibition mechanism of RDP-p53 according to the data of flow cytometric analysis. Conclusions : RDP-p53 could be a novel antitumor candidate for targeting treatment of cancerous neural cells.